2020
DOI: 10.1088/2053-1591/ab7f5d
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ti on microstructure and mechanical properties of die-cast Al-Mg-Zn-Si alloy

Abstract: The Al-11.0Mg-2.6Si-4.0Zn-0.6Mn (wt%) alloy is a new developed high strength die cast alloy which can be used for structural parts in the automotive and aerospace industry. In this study, the effect of various amount of Ti on microstructure evolution and mechanical properties of Al-11.0Mg-2.6Si-4.0Zn-0.6Mn (wt%) alloy under as-cast and T6 heat treatment conditions are investigated. The addition of Ti results in the formation of Al 3 Ti intermetallic phase, and the volume fraction and forming temperature increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…This behavior agrees with the result which obtained by Jaradeh et al [26], where not all Ti3Al particles are dissolved. Zhang et al [27] found that excess Ti addition tend to form large particles of Ti3Al intermetallic.…”
Section: Results and Discussion Joint Addition Of 01 % Zr And Variomentioning
confidence: 99%
“…This behavior agrees with the result which obtained by Jaradeh et al [26], where not all Ti3Al particles are dissolved. Zhang et al [27] found that excess Ti addition tend to form large particles of Ti3Al intermetallic.…”
Section: Results and Discussion Joint Addition Of 01 % Zr And Variomentioning
confidence: 99%
“…According to duplex nucleation theory, the nuclei in crystallization are TiB 2 particles with thin TiAl 3 layers [14]. The TiAl 3 intermetallic particles may function as nucleating agents for α-Al crystals [15]. Ding et al [16] found that the arrangement of grain refinement characteristics in commercial aluminum was altered by incorporating Al-5Ti master alloys with variable sizes, morphologies, and intermetallic TiAl 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a low-carbon society/carbon-free society has been a focus in realizing a sustainable world. Many innovative technologies, such as new generation thermal plants 1) and light-metal alloy manufacturing, [2][3][4] have been developed. New technology often causes unexpected phenomena, so real time process monitoring during operation has been desired to achieve safety and efficiency, simultaneously.…”
Section: Introductionmentioning
confidence: 99%